Detection of time-varying pulsed event effects on estuarine pelagic communities with ecological indicators after catastrophic hurricanes - Liu, Hui; Gilmartin, Jillian; Li, Chengxue; Li, Kaizhi (Ecological indicators, 2021)
•Near-term changes in zooplankton communities were mainly caused by massive flooding.•Zooplankton abundance showed fast recovery and persistence of pulsed event effects.•Spatial zooplankton ordinations disclosed long-term hurricane impacts to the bay.•Floods were more harmful than storm surge with ecosystem implications to estuaries. Tropical storm-related pulsed events in estuarine and coastal ecosystems have drawn increased attention to seek mechanisms for mitigating the aftermath of climate-driven natural disasters on community structure and ecosystem functions. Over the last few decades, two major hurricanes struck one of the largest estuaries in the Gulf of Mexico (Galveston Bay, Texas, USA) with the relatively remarkable magnitude of disturbances from the storm surge of Hurricane Ike in 2008 and the torrential rainfall and floods associated with Hurricane Harvey in 2017, which provided a natural experiment to examine the community resilience and ecosystem recovery in terms of external perturbations. Using a set of estuarine ecological indicators collected before and after the two hurricanes, we examined time-varying impacts of hurricanes on estuarine pelagic communities including hydrography, zooplankton and juvenile fish, estimated the recovery of zooplankton communities, and explored the relative importance of storm surge and floods with potential implications for the estuarine ecosystem function. Our findings showed: (1) significant acute changes in zooplankton community structure a few days after hurricanes mainly reflected the extreme floodwater discharge and intense physical actions; (2) zooplankton abundance displayed relatively faster recovery than the community structure and persistence of pulsed effects after hurricanes; (3) aftermaths of the two hurricanes exhibited distinct spatial arrangements of zooplankton assemblages associated with hydrographic factors largely signifying the relative impact of floodwater discharge and storm surge on pelagic communities; (4) extreme flooding appeared more devastating than storm surging with significant implications to community resiliency and functions of estuarine ecosystems. Given the predicted increasing frequency and intensity of hurricane activities, this study contributes to the improved understandings of hurricane-induced estuarine pelagic dynamics in support of better restoration and management of estuarine ecosystems in the face of anticipated climate-driven future disasters.